(untitled) (Strojniški vestnik – Journal of Mechanical Engineering, 2024)
This research analyzes failure mechanisms of mechanical components subjected to extreme environmental conditions. Numerical simulation techniques were used to investigate stress concentration, deformation behavior, and damage evolution. The findings provide valuable guidance for improving component safety and durability.